Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada LPK OTC Bali Gianyar - Suhati, Luh Wawas; Kartimin, I Wayan; Yuda, Ida Bagus Nyoman Krisna Prawira (Universitas Triatma Mulya, 2025)
This research is entitled The Effect of Work Environment and Workload on Employee Performance at LPK OTC Bali Gianyar which aims to analyze the Effect of Work Environment and Workload on Employee Performance partially and simultaneously. This research is a population research because it uses a total of 57 employees at LPK OTC Bali Gianyar. The analysis techniques used are descriptive analysis, classical assumption test, correlation analysis, multiple linear regression analysis and hypothesis testing (T test and F test). The results of statistical analysis show that the Work Environment (XI) partially and significantly influences the performance of LPK OTC Bali Gianyar employees. It can be seen that the T-count value is < T-table and the Sig value is > 0.05%. Workload (X2) has a positive and significant influence on employee performance, this can be seen from the T-count > T-table value and the Sig value < 0.05%. Other information obtained is that the Work Environment (X1) and Workload (X2) have a positive and significant influence on employee performance (Y) LPK OTC Bali Gianyar, this is confirmed using the F test, obtained F Calculated = 58,873 > F Table = 3.07 with Sig.F = 0.002 (p<0.05).